Electrolytic capacitor and method for manufacturing electrolytic capacitor

By using a combination of π-conjugated polymer and quinone compound in the solid electrolyte layer of the electrolytic capacitor, the problems of electrolyte layer deterioration and ESR increase at high temperatures are solved, and the heat resistance and conductivity of the electrolytic capacitor are improved.

CN112151277BActive Publication Date: 2025-01-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010576848.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-22
Publication Date
2025-01-10
Estimated Expiration
2040-06-22

AI Technical Summary

Technical Problem

The solid electrolyte layer of the electrolytic capacitor is prone to deterioration under high temperature conditions, resulting in an increase in equivalent series resistance (ESR), affecting its conductivity and heat resistance.

Method used

A conductive material containing a π-conjugated polymer and a polymer dopant having a first anionic group is used, and a quinone compound having a second anionic group is added thereto to form a solid electrolyte layer to suppress high height. Dedoping of molecular dopants and rising ESR.

Benefits of technology

The heat resistance of the electrolytic capacitor is significantly improved, the deterioration of the solid electrolyte layer and the rise of ESR are suppressed, high conductivity and low ESR are maintained, and the voltage withstand characteristics of the capacitor are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112151277B_ABST
    Figure CN112151277B_ABST
Patent Text Reader

Abstract

The present invention provides an electrolytic capacitor with excellent heat resistance. The electrolytic capacitor has an anode body having a dielectric layer on the surface, and a solid electrolyte layer. The solid electrolyte layer contains a conductive material and an additive. The conductive material contains a π-conjugated polymer and a polymer dopant having a first anionic group doped in the π-conjugated polymer. The additive contains a quinone compound having a second anionic group. The present invention also relates to a method for manufacturing an electrolytic capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolytic capacitor having a solid electrolyte layer and a method for manufacturing the same. Background Art

[0002] The electrolytic capacitor comprises an anode body having a dielectric layer formed on the surface thereof and a solid electrolyte layer formed so as to cover at least a portion of the dielectric layer. The solid electrolyte layer comprises a π-conjugated polymer and a dopant doped in the π-conjugated polymer. As the dopant, a polymer organic acid such as polystyrene sulfonic acid which can exhibit high conductivity and low equivalent series resistance (ESR) is often used (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-17230 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Electrolytic capacitors may be exposed to high temperatures due to, for example, heat generated when a ripple current is applied or heating during soldering by a reflow method. When an electrolytic capacitor is exposed to high temperatures, the solid electrolyte layer may deteriorate and the ESR may increase.

[0008] Solutions to Solve Problems

[0009] One embodiment of the present invention relates to an electrolytic capacitor, comprising a solid electrolyte layer and an anode body having a dielectric layer on the surface, wherein the solid electrolyte layer contains a conductive material and an additive, the conductive material contains a π-conjugated polymer and a polymer dopant having a first anionic group doped in the π-conjugated polymer, and the additive contains a quinone compound having a second anionic group.

[0010] Another embodiment of the present invention relates to a method for manufacturing an electrolytic capacitor, which comprises the following steps: a first step of preparing a conductive material comprising a π-conjugated polymer and a polymer dopant having an anionic group doped in the π-conjugated polymer; a second step of obtaining a treatment solution comprising the conductive material and a quinone compound having an anionic group as an additive; and a third step of impregnating the treatment solution into at least a portion of the dielectric layer of an anode body having a dielectric layer on its surface, thereby forming a solid electrolyte layer.

[0011] Effects of the Invention

[0012] According to the present invention, an electrolytic capacitor having excellent heat resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention.

[0014] Figure 2 It is a schematic diagram for explaining the structure of the capacitor element of this embodiment.

[0015] Description of Reference Numerals

[0016] 10: capacitor element; 11: bottom shell; 12: sealing member; 13: seat plate; 14A, 14B: lead wire; 15A, 15B: lead wire connector; 21: anode body; 22: cathode body; 23: spacer; 24: sealing tape DETAILED DESCRIPTION

[0017] [Electrolytic capacitors]

[0018] The electrolytic capacitor described in the embodiment of the present invention comprises an anode body having a dielectric layer on the surface, and a solid electrolyte layer. The solid electrolyte layer is formed on the dielectric layer. The solid electrolyte layer comprises a conductive material and an additive. The conductive material comprises a π-conjugated polymer and a polymer dopant having a first anionic group. The polymer dopant is doped in the π-conjugated polymer. The additive comprises a quinone compound having a second anionic group (hereinafter also referred to as a quinone compound). The quinone compound does not need to be doped in the π-conjugated polymer. The amount of dopant that can be doped in the π-conjugated polymer is generally limited. The sites of the π-conjugated polymer that can interact with the dopant can be in a state of being saturated with the polymer dopant having the first anionic group.

[0019] By including a quinone compound in the solid electrolyte layer, the degradation of the solid electrolyte layer and the increase in ESR associated therewith when the electrolytic capacitor is exposed to high temperature are suppressed. The detailed reason is not clear, but it is presumed that the presence of the quinone compound near the conductive material in the solid electrolyte layer suppresses the dedoping of the polymer dopant from the π-conjugated polymer.

[0020] The conductive material containing the polymer dopant is advantageous in terms of having high conductivity and low ESR. From the viewpoint of ensuring a sufficient amount of conductive material in the solid electrolyte layer, it is desirable that the amount of the quinone compound contained in the solid electrolyte layer is a small amount that can suppress the dedoping of the polymer dopant. That is, it is desirable that the amount of the quinone compound in the solid electrolyte layer is less than the amount of the polymer dopant. From the viewpoint of maintaining high conductivity and low ESR, in the solid electrolyte layer, the amount of the quinone compound is preferably, for example, 1 part by mass or more and 40 parts by mass or less relative to 100 parts by mass of the polymer dopant.

[0021] The content of the quinone compound in the solid electrolyte layer is, for example, 0.1 mass parts or more and 35 mass parts or less, preferably 1 mass parts or more and 30 mass parts or less, and more preferably 5 mass parts or more and 25 mass parts or less, relative to every 100 mass parts of the conductive material. When the content of the quinone compound in the solid electrolyte layer is 1 mass part or more relative to every 100 mass parts of the conductive material, the inhibitory effect of the rise of ESR becomes larger. When the content of the quinone compound in the solid electrolyte layer is 30 mass parts or less relative to every 100 mass parts of the conductive material, it is easy to maintain a higher conductivity of the solid electrolyte layer.

[0022] (Quinone Compounds)

[0023] The quinone compound is an aromatic compound having a quinone structure (a ring structure containing at least two carbonyl groups).

[0024] As the second anionic group of the quinone compound, a sulfonic acid group, a carboxyl group, a phosphoric acid group, a phosphonic acid group, etc. can be mentioned. The quinone compound can have one anionic group, or it can have two or more. As the anionic group, a sulfonic acid group is preferred, or it can be a combination of a sulfonic acid group and an anionic group other than a sulfonic acid group. For example, the quinone compound can be a monosulfonic acid, a disulfonic acid, or a trisulfonic acid.

[0025] Examples of the quinone compound include anthraquinone compounds, naphthoquinone compounds, and benzoquinone compounds. Among the quinone compounds, anthraquinone compounds are particularly preferred. The quinone compounds may be used alone or in combination of two or more.

[0026] The anthraquinone compound is preferably an anthraquinone compound having a sulfonic acid group, and examples thereof include compounds having a structure represented by the following general formula (1).

[0027] [Chemical formula 1]

[0028]

[0029] R in formula (1) 1 ~R 8 Any one of, or R 1 ~R 4 Any one and R 5 ~R 8 Any one of is a sulfonic acid group. 1 ~R 8 In the above, the remaining groups other than the sulfonic acid group are each independently a hydrogen atom or a substituent other than a hydrogen atom. Examples of the substituent include a halogen atom, a hydroxyl group, an amino group, an alkyl group, an alkoxy group, and an alkylamino group. The number of carbon atoms of the alkyl group (including the alkyl group included in the alkoxy group and the alkylamino group) is, for example, 1 to 5. The alkylamino group may be a monoalkylamino group or a dialkylamino group. Some of the hydrogen atoms of the alkyl group may be substituted by halogen atoms or the like.

[0030] More specifically, examples of the anthraquinone compound having a sulfonic acid group include anthraquinone-1-sulfonic acid, anthraquinone-2-sulfonic acid, anthraquinone-2,6-disulfonic acid, anthraquinone-2,7-disulfonic acid, anthraquinone-1,5-disulfonic acid, and 2-methylanthraquinone-6-sulfonic acid. Anthraquinone-1-sulfonic acid, anthraquinone-2-sulfonic acid, anthraquinone-2,6-disulfonic acid, anthraquinone-2,7-disulfonic acid, and anthraquinone-1,5-disulfonic acid are particularly preferred.

[0031] As the naphthoquinone compound, a naphthoquinone compound having a sulfonic acid group is preferred, and examples thereof include compounds having a structure represented by the following general formula (2).

[0032] [Chemical formula 2]

[0033]

[0034] R in formula (2) 11 ~R 16 Any one of is a sulfonic acid group. 11 ~R 16 In the formula (1), the remaining groups other than the sulfonic acid group are each independently a hydrogen atom or a substituent other than a hydrogen atom. 1 ~R 8 Those exemplified in the substituents of .

[0035] More specifically, examples of the naphthoquinone compound having a sulfonic acid group include 1,4-naphthoquinone-2-sulfonic acid and 1,2-naphthoquinone-4-sulfonic acid, of which 1,2-naphthoquinone-4-sulfonic acid is particularly preferred.

[0036] The benzoquinone compound is preferably a benzoquinone compound having a sulfonic acid group, and examples thereof include compounds having structures represented by the following general formula (3) and general formula (4).

[0037] [Chemical formula 3]

[0038]

[0039] [Chemical formula 4]

[0040]

[0041] R in formula (3) 21 ~R 24 Any one of and R in formula (4) 31 ~R 34 Any one of is a sulfonic acid group. 21 ~R 24 and R 31 ~R 34In the formula (1), the remaining groups other than the sulfonic acid group are each independently a hydrogen atom or a substituent other than a hydrogen atom. 1 ~R 8 Those exemplified in the substituents of .

[0042] More specifically, the benzoquinone compound having a sulfonic acid group is preferably 1,4-benzoquinone-2-sulfonic acid or 1,2-benzoquinone-4-sulfonic acid.

[0043] (π-conjugated polymer)

[0044] As the π-conjugated polymer, polypyrrole, polythiophene, polyaniline, etc. are preferred. They can be used alone, two or more can be used in combination, or they can be copolymers of two or more monomers. By adding a quinone compound to the solid electrolyte layer containing such a π-conjugated polymer, the rise of ESR can be suppressed.

[0045] It should be noted that in this specification, polypyrrole, polythiophene, polyaniline, etc. respectively refer to polymers having polypyrrole, polythiophene, polyaniline, etc. as basic skeletons. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT), etc.

[0046] The weight average molecular weight of the π-conjugated polymer is not particularly limited, and may be, for example, 1,000 to 100,000.

[0047] (Polymer dopant)

[0048] As the first anionic group of the polymer dopant, those exemplified in the quinone compound can be used.

[0049] As the polymer dopant, anions of polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polymethallyl sulfonic acid, poly(2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, etc. can be cited. They can be used alone or in combination of two or more. In addition, they can be homopolymers or copolymers of two or more monomers. Polystyrene sulfonic acid (PSS) is particularly preferred.

[0050] The weight average molecular weight of the polymer dopant is not particularly limited, but is preferably, for example, 1,000 to 100,000 from the viewpoint of easily forming a homogeneous solid electrolyte layer.

[0051] (liquid component a)

[0052] The electrolytic capacitor may include a liquid component a. The liquid component a can be used in a solvent of an electrolyte solution described later. The liquid component a preferably includes a diol compound and / or a glycerol compound (hereinafter also referred to as a diol compound, etc.). By including a diol compound, etc. in the liquid component a, the orientation or crystallinity of the π-conjugated polymer contained in the solid electrolyte layer is improved. As a result, the conductivity of the solid electrolyte layer increases, and the ESR of the electrolytic capacitor decreases. In addition, the contact between the solid electrolyte layer and the dielectric layer increases, and the withstand voltage characteristics also increase.

[0053] When the electrolytic capacitor is exposed to high temperature, sometimes the liquid components such as diol compounds are reduced, and the effect of increasing the orientation of π-conjugated polymers is reduced. On the other hand, when the solid electrolyte layer contains quinone compounds, even if the diol compounds are reduced, the effect of increasing the orientation of π-conjugated polymers is maintained. The detailed reason is not clear, but even in a high temperature atmosphere, quinone compounds are present near π-conjugated polymers and polymer dopants, so that even if the liquid components such as diol compounds are reduced, the orientation of π-conjugated polymers is maintained. It is speculated that as a result, the increase in ESR is suppressed and the conductivity of the solid electrolyte layer does not decrease.

[0054] The total ratio of the diol compound and the glycerin compound contained in the liquid component a is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.

[0055] The glycol compound includes ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and polyalkylene glycols having a molecular weight of about 190 to 400. The glycerol compound includes glycerol, polyglycerol, etc. The polymerization degree of polyglycerol is preferably 2 or more and 20 or less.

[0056] The diol compound preferably includes ethylene glycol. In addition, when the liquid component a includes multiple diol compounds, it is desirable that ethylene glycol is the main component of the diol compound. Since ethylene glycol has a particularly low viscosity among diol compounds, it is easy to dissolve the solute of the electrolyte. In addition, since ethylene glycol has high thermal conductivity and excellent heat release when ripple current is generated, the effect of increasing heat resistance is also large.

[0057] The proportion of ethylene glycol in the diol compound is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. The diol compound may be 100% by mass of ethylene glycol.

[0058] (Electrolyte)

[0059] The electrolytic capacitor may include an electrolyte. By using an electrolyte, an electrolytic capacitor having excellent repair function of the dielectric layer can be obtained. The electrolyte includes a solvent and a solute, and the solvent may include a liquid component a. The solute may include an acid component and an alkaline component. From the viewpoint of suppressing the degradation of the solid electrolyte layer, more acid components may be included than alkaline components. The molar ratio of the acid component to the alkaline component: (acid component / alkaline component) may be, for example, 1.0 to 10.0.

[0060] As the acid component, organic acid, inorganic acid, composite compound of organic acid and inorganic acid, etc. can be used. As organic acid, carboxylic acid compounds, etc. can be used. As carboxylic acid compounds, phthalic acid (ortho-body), isophthalic acid (meta-body), terephthalic acid (para-body), maleic acid, benzoic acid, salicylic acid, methyl benzoic acid, trimellitic acid, pyromellitic acid, adipic acid, heptanoic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, oxalic acid, glycolic acid, etc. can be mentioned. From the viewpoint of the repair function and thermal stability of the dielectric layer of the electrolyte, phthalic acid is particularly preferred. As inorganic acid, boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphate ester, carbonic acid, silicic acid, etc. can be mentioned. As composite compounds, boron disalicylic acid, boron diglycolic acid, boron dioxalic acid, etc. can be mentioned.

[0061] As the base component, an amine compound or the like can be used. As the amine compound, primary to tertiary amine compounds can be mentioned. Specifically, as the amine compound, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, hexamethylenediamine, spermidine, spermine, adamantane amine, aniline, phenethylamine, toluidine, pyrrolidine, piperidine, piperazine, morpholine, imidazole, pyridine, pyridazine, pyrimidine, pyrazine, 4-dimethylaminopyridine, etc. can be mentioned. They can be used alone or in combination of two or more. Tertiary amines such as triethylamine and monoethyldimethylamine are particularly preferred.

[0062] The solvent may include the above-mentioned diol compound, the above-mentioned glycerol compound, sulfone compound, lactone compound, carbonate compound, etc. As the sulfone compound, cyclopentane, dimethyl sulfoxide, diethyl sulfoxide, etc. may be used. As the lactone compound, γ-butyrolactone, γ-valerolactone, etc. may be used. As the carbonate compound, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), etc. may be used. They may be used alone or in combination.

[0063] [Method for manufacturing electrolytic capacitor]

[0064] The method for manufacturing an electrolytic capacitor according to an embodiment of the present invention includes the following steps 1 to 3. The first step is a step of preparing a conductive material including a π-conjugated polymer and a polymer dopant having a first anionic group doped in the π-conjugated polymer. The second step is a step of obtaining a treatment solution including a conductive material and a quinone compound having a second anionic group as an additive. The third step is a step of forming a solid electrolyte layer by impregnating the treatment solution into at least a portion of the dielectric layer of an anode body having a dielectric layer on the surface.

[0065] The above-mentioned manufacturing method can form a solid electrolyte layer including a conductive material and an undoped quinone compound. Since the quinone compound is added after the polymer dopant is doped into the π-conjugated polymer, the quinone compound can be included in the solid electrolyte layer in an undoped state.

[0066] (1st step)

[0067] In the first step, the conductive material can be prepared in the form of a polymer dispersion. The polymer dispersion includes a liquid component b and the conductive material dispersed in the liquid component b. The polymer dispersion can be a solution in which the conductive material is dissolved in the liquid component b, or a dispersion in which particles of the conductive material are dispersed in the liquid component b.

[0068] The polymer dispersion can be prepared, for example, by dispersing a conductive material in a liquid component b. In addition, the polymer dispersion can be prepared according to the following steps. Precursor monomers are polymerized in a liquid component b containing a polymer dopant and an oxidant. A π-conjugated polymer is synthesized from the precursor monomers and the polymer dopant is doped into the conjugated polymer to generate particles of a conductive material. The reaction solution is dialyzed to remove unreacted monomers and excess oxidant. As a conductive material, for example, poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonic acid (PSS), i.e., PEDOT / PSS, can be cited.

[0069] Liquid component b can be water, a non-aqueous solvent, or a mixture of water and a non-aqueous solvent. The non-aqueous solvent is not particularly limited, and for example, a protic solvent or an aprotic solvent can be used. As protic solvents, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, propylene glycol, formaldehyde, ethers such as 1,4-dioxane, etc. can be exemplified. As aprotic solvents, amides such as N-methylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, esters such as methyl acetate, ketones such as methyl ethyl ketone, etc. can be exemplified.

[0070] (Second step)

[0071] The treatment liquid obtained in the second step contains, for example, a liquid component b, a conductive material, and a quinone compound. In the second step, the treatment liquid can be obtained by adding a quinone compound to the polymer dispersion (liquid component b containing a conductive material) prepared in the first step. In addition, the treatment liquid can be obtained by adding a liquid component b containing a quinone compound to the polymer dispersion prepared in the first step.

[0072] The concentration of the conductive material in the treatment liquid is preferably, for example, 0.5 to 10% by mass. In addition, the average particle size D50 of the conductive material is preferably, for example, 0.01 to 0.5 μm. Here, the average particle size D50 is the median particle size in the volume particle size distribution obtained by a particle size distribution measuring device based on a dynamic light scattering method. Such a concentration of the treatment liquid is suitable for forming a solid electrolyte layer of appropriate thickness and is easy to infiltrate into the dielectric layer.

[0073] (Step 3)

[0074] In the third step, a treatment liquid containing a conductive material and an additive is infiltrated into at least a portion of the dielectric layer to form a solid electrolyte layer. The solid electrolyte layer is formed in a manner that covers at least a portion of the dielectric layer. In the third step, a liquid component b containing a conductive material and an additive can be attached to the surface of the dielectric layer to form a film, and dried, thereby volatilizing at least a portion of the liquid component b from the formed film. In this way, a dense solid electrolyte layer covering at least a portion of the dielectric layer is formed.

[0075] Hereinafter, the present invention will be described in more detail based on the embodiments thereof. However, the present invention is not limited to the following embodiments.

[0076] Figure 1 is a schematic cross-sectional view of an electrolytic capacitor according to this embodiment, Figure 2 This is a schematic diagram showing a portion of a capacitor element of the electrolytic capacitor being developed.

[0077] The electrolytic capacitor includes, for example, a capacitor element 10; a bottomed case 11 that accommodates the capacitor element 10; a sealing member 12 that seals the opening of the bottomed case 11; a seat plate 13 that covers the sealing member 12; leads 14A and 14B that are led out of the sealing member 12 and pass through the seat plate 13; lead terminals 15A and 15B that connect the leads to electrodes of the capacitor element 10; and an electrolyte (not shown). The opening end of the bottomed case 11 is necked inward, and the opening end is curled in a manner riveted to the sealing member 12.

[0078] The sealing member 12 is formed of an elastic material containing a rubber component. As the rubber component, butyl rubber (IIR), nitrile rubber (NBR), ethylene propylene rubber, ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), isoprene rubber (IR), chlorosulfonated polyethylene (Hypalon) rubber, silicone rubber, fluororubber, etc. can be used. The sealing member 12 may contain fillers such as carbon black and silica.

[0079] The capacitor element 10 is composed of Figure 2 The wound body is produced. The wound body is a semi-finished product of the capacitor element 10 in which a solid electrolyte is not formed between the anode body 21 and the cathode body 22 having a dielectric layer on the surface. The wound body includes: the anode body 21 connected to the lead tab 15A, the cathode body 22 connected to the lead tab 15B, and the separator 23.

[0080] The anode body 21 and the cathode body 22 are wound with the separator 23 interposed therebetween. The outermost periphery of the wound body is fixed by a sealing tape 24. Figure 2 The partially unwound state is shown before the outermost circumference of the wound body is fixed.

[0081] The anode body 21 has a metal foil which has been roughened to have a concavo-convex surface, and a dielectric layer is formed on the concavo-convex metal foil. A solid electrolyte layer is formed by attaching a conductive material to at least a portion of the surface of the dielectric layer. The solid electrolyte may cover at least a portion of the surface of the cathode body 22 and / or the surface of the separator 23. The capacitor element 10 formed with the solid electrolyte layer is contained in an outer casing together with an electrolyte.

[0082] Hereinafter, an example of a method for manufacturing an electrolytic capacitor according to the present embodiment will be described step by step.

[0083] (i) Step of Preparing Anode Body 21 Having Dielectric Layer

[0084] First, a metal foil is prepared as a raw material of anode body 21. The type of metal is not particularly limited, but valve metals such as aluminum, tantalum, and niobium, or alloys containing valve metals are preferably used from the viewpoint of facilitating formation of a dielectric layer.

[0085] Next, the surface of the metal foil is roughened. The roughening forms a plurality of concavities and convexities on the surface of the metal foil. The roughening is preferably performed by etching the metal foil. The etching can be performed by, for example, direct current electrolysis or alternating current electrolysis.

[0086] Next, a dielectric layer is formed on the surface of the roughened metal foil. The formation method is not particularly limited, and the dielectric layer can be formed by subjecting the metal foil to a chemical conversion treatment. In the chemical conversion treatment, for example, the metal foil is immersed in a chemical conversion liquid such as an ammonium adipate solution and subjected to a heat treatment. Alternatively, the metal foil may be immersed in a chemical conversion liquid and a voltage may be applied.

[0087] Generally, from the viewpoint of mass productivity, a large foil (metal foil) of a valve metal or the like is subjected to a roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut into a desired size to prepare the anode body 21 .

[0088] (ii) Step of Preparing Cathode Body 22

[0089] The cathode body 22 can be made of metal foil, similarly to the anode body 21. The type of metal is not particularly limited, but preferably a valve metal such as aluminum, tantalum, niobium, or an alloy containing a valve metal is used. The surface of the cathode body 22 may be roughened as needed. In addition, a carbon layer, a metal layer such as titanium, nickel, or a metal oxide layer such as aluminum oxide or titanium oxide may be formed on the surface of the cathode body 22.

[0090] (iii) Preparation of wound body

[0091] Next, a wound body is produced using anode body 21 and cathode body 22 .

[0092] First, the anode body 21 and the cathode body 22 are wound with the separator 23 interposed therebetween. At this time, the winding is performed while the lead tabs 15A and 15B are wound in, so that the anode body 21 and the cathode body 22 can be wound as shown in FIG. Figure 2 As shown, lead terminals 15A, 15B are provided upright from the wound body.

[0093] As the material of the spacer 23, for example, nonwoven fabric mainly composed of synthetic cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like can be used.

[0094] Next, a sealing tape 24 is placed on the outer surface of the cathode body 22, which is the outermost layer among the wound anode body 21, cathode body 22, and separator 23, and the end of the cathode body 22 is fixed with the sealing tape 24. It should be noted that when the anode body 21 is prepared by cutting a large sheet of metal foil, the wound body may be further subjected to a chemical treatment in order to provide a dielectric layer on the cut surface of the anode body 21.

[0095] (iv) Step of Forming Capacitor Element 10

[0096] Next, a treatment solution containing a conductive material and a quinone compound is prepared, and the treatment solution is impregnated into the dielectric layer to form a film covering at least a portion of the dielectric layer. As a method of applying the treatment solution to the surface of the dielectric layer, for example, a method of immersing the wound body in the treatment solution contained in a container is simple and preferred. The immersion time varies depending on the size of the wound body, for example, it is 1 second to 5 hours, preferably 1 minute to 30 minutes. In addition, the impregnation is preferably carried out in an atmosphere of reduced pressure, for example, 10 to 100 kPa, preferably 40 to 100 kPa. In addition, ultrasonic vibration can be applied to the wound body or the treatment solution while being immersed in the treatment solution. Drying after the wound body is lifted out of the treatment solution is preferably carried out at, for example, 50 to 300°C, more preferably at 100 to 200°C.

[0097] The process of applying the treatment liquid to the surface of the dielectric layer and the process of drying the wound body can be repeated two or more times. By performing these processes multiple times, the coverage of the solid electrolyte layer on the dielectric layer can be increased. At this time, the solid electrolyte layer can be formed not only on the surface of the dielectric layer, but also on the surface of the cathode body 22 separator 23.

[0098] As described above, a solid dielectric layer can be formed between anode body 21 and cathode body 22 to produce capacitor element 10. It should be noted that the solid electrolyte layer formed on the surface of the dielectric layer actually functions as a cathode material.

[0099] (v) Step of impregnating capacitor element 10 with electrolyte solution

[0100] Next, the capacitor element 10 is impregnated with the electrolyte. Thus, an electrolytic capacitor having excellent repair function of the dielectric layer can be obtained. The method of impregnating the capacitor element 10 with the electrolyte is not particularly limited. For example, a method of immersing the capacitor element 10 in the electrolyte contained in a container is simple and preferred. The immersion time varies depending on the size of the capacitor element 10, for example, 1 second to 5 minutes. The impregnation is preferably carried out in an atmosphere under reduced pressure, for example 10 to 100 kPa, preferably 40 to 100 kPa.

[0101] (vi) Step of sealing the capacitor element

[0102] Next, capacitor element 10 is sealed. Specifically, capacitor element 10 is first housed in bottomed case 11 so that leads 14A and 14B are located on the upper surface of the opening of bottomed case 11. As a material for bottomed case 11, metals such as aluminum, stainless steel, copper, iron, and brass, or alloys thereof can be used.

[0103] Next, the sealing member 12 formed so as to penetrate the lead wires 14A and 14B is arranged above the capacitor element 10, and the capacitor element 10 is sealed in the bottom case 11. Next, the open end of the bottom case 11 is subjected to transverse necking processing, and the open end is riveted to the sealing member 12 and curled. Then, the seat plate 13 is arranged on the curled portion, thereby completing the Figure 1 The electrolytic capacitor shown in the figure can then be aged while applying the rated voltage.

[0104] In the above embodiment, a wound electrolytic capacitor is described, but the application scope of the present invention is not limited to the above content, and can also be applied to other electrolytic capacitors, such as a chip-type electrolytic capacitor using a metal sintered body as an anode body, and a stacked electrolytic capacitor using a metal plate as an anode body.

[0105] [Example]

[0106] The present invention will be described in further detail below based on examples, but the present invention is not limited to the examples.

[0107] 《Example 1》

[0108] In this embodiment, a wound electrolytic capacitor (Φ10.0 mm×L (length) 10.0 mm) having a rated voltage of 25 V and a rated electrostatic capacity of 330 μF is manufactured. A specific method for manufacturing the electrolytic capacitor is described below.

[0109] (Preparation of anode body)

[0110] An aluminum foil having a thickness of 100 μm was etched to roughen the surface of the aluminum foil. Thereafter, the surface of the aluminum foil was subjected to a chemical conversion treatment to form a dielectric layer. The chemical conversion treatment was performed by immersing the aluminum foil in an ammonium adipate solution and applying a voltage of 45 volts thereto. Thereafter, the aluminum foil was cut into a size of 8 mm × 120 mm in length × width to prepare an anode body.

[0111] (Preparation of cathode body)

[0112] An aluminum foil having a thickness of 50 μm was etched to roughen the surface of the aluminum foil, and then the aluminum foil was cut into a size of 8 mm in length and 120 mm in width to prepare a cathode body.

[0113] (Production of wound body)

[0114] The anode lead connector and the cathode lead connector are connected to the anode body and the cathode body, and the anode body and the cathode body are wound with the separator interposed therebetween while the lead connectors are wound in. The anode lead and the cathode lead are respectively connected to the ends of the lead connectors protruding from the wound body. Then, the wound body is subjected to a chemical forming treatment again, and a dielectric layer is formed at the cut end of the anode body. Next, the end of the outer surface of the wound body is fixed with a sealing tape, thereby manufacturing the wound body.

[0115] (Preparation of polymer dispersion containing conductive material)

[0116] 3,4-ethylenedioxythiophene and poly(4-styrenesulfonic acid) (PSS, weight average molecular weight of 100,000) as a polymer dopant are dissolved in ion exchange water (liquid component b) to prepare a mixed solution. While stirring the mixed solution, iron (III) sulfate (oxidant) dissolved in ion exchange water is added to perform a polymerization reaction. After the reaction, the obtained reaction solution is dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a polymer dispersion containing poly(3,4-ethylenedioxythiophene) (PEDOT / PSS) doped with PSS as a conductive material.

[0117] (Preparation of a treatment solution containing a conductive material and an additive)

[0118] In the polymer dispersion containing the conductive material (PEDOT / PSS) obtained above, 20 parts by mass of anthraquinone-2-sulfonic acid (AQS) as an additive was added per 100 parts by mass of the conductive material to obtain a treatment liquid containing the conductive material and the additive. It should be noted that the amount of AQS added was 30 parts by mass per 100 parts by mass of PSS.

[0119] (Formation of Solid Electrolyte Layer)

[0120] The wound body was immersed in a treatment liquid contained in a predetermined container in a reduced pressure atmosphere (40 kPa) for 5 minutes, and then the wound body was lifted out of the treatment liquid. Next, the wound body impregnated with the treatment liquid was dried in a drying oven at 150° C. for 20 minutes to form a solid electrolyte layer covering at least a portion of the dielectric layer.

[0121] (Impermeation of electrolyte)

[0122] The solvent of the electrolytic solution used was a mixed solvent containing ethylene glycol (EG) as a diol compound (liquid component a) and γ-butyrolactone (GBL) as a lactone compound at a volume ratio of 50:50.

[0123] Phthalic acid (ortho-form) as an organic carboxylic acid compound was used as the acid component of the solute. Triethylamine as an amine compound was used as the base component of the solute. An electrolyte solution was prepared using the above-mentioned solvent and solute.

[0124] The content of the solute relative to the entire electrolyte was set to 10% by mass. The molar ratio of the acid component to the alkali component: (acid component / alkali component) was set to 1 / 1. It should be noted that at least a portion of the acid component (phthalic acid) was added in the form of a salt (triethylamine phthalate) with the alkali component (triethylamine).

[0125] The capacitor element was immersed in the electrolyte solution in a reduced pressure atmosphere (40 kPa) for 5 minutes.

[0126] (Sealing of capacitor elements)

[0127] The capacitor element impregnated with electrolyte is sealed to complete the electrolytic capacitor. Specifically, the capacitor element is housed in the bottomed shell in such a way that the lead wire is located on the open side of the bottomed shell, and a sealing component (an elastic material containing butyl rubber as a rubber component) formed in such a way that the lead wire passes through is arranged above the capacitor element, thereby sealing the capacitor element in the bottomed shell. Then, a necking process is performed near the open end of the bottomed shell, and then the open end is curled, and a seat plate is arranged on the curled portion, thereby completing Figure 1 Then, an aging treatment was performed at 130° C. for 2 hours while applying the rated voltage.

[0128] [evaluate]

[0129] The electrolytic capacitor A1 produced as described above was evaluated as follows.

[0130] The electrolytic capacitor after aging was subjected to reflow treatment twice for 10 seconds at a peak temperature of 260±5° C. The ESR value (initial ESR value: X0) (Ω) of the electrolytic capacitor after reflow treatment was measured at a frequency of 100 kHz using an LCR meter in an environment of 20° C.

[0131] After measuring X0, a high temperature load test was performed. That is, the rated voltage was applied to the electrolytic capacitor at a temperature of 145°C for 1000 hours. The ESR value (X1) (Ω) of the electrolytic capacitor after the high temperature load test was measured by the same method as above.

[0132] Using the obtained X0 and X1, the ESR increase rate (ΔESR) was calculated from the following formula.

[0133] ΔESR(%)==(X1 / X0)×100

[0134] Comparative Example 1

[0135] An electrolytic capacitor B1 was produced and evaluated in the same manner as in Example 1, except that the additive (AQS) was not added to the polymer dispersion containing the conductive material (PEDOT / PSS).

[0136] Comparative Example 2

[0137] 3,4-ethylenedioxythiophene and AQS as a low molecular weight dopant are dissolved in ion exchange water (liquid component) to prepare a mixed solution. While stirring the mixed solution, iron (III) sulfate (oxidant) dissolved in ion exchange water is added to perform a polymerization reaction. After the reaction, the obtained reaction solution is dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a polymer dispersion containing poly (3,4-ethylenedioxythiophene) (PEDOT / AQS) doped with AQS as a conductive material.

[0138] An electrolytic capacitor B2 was produced and evaluated in the same manner as in Example 1, except that a polymer dispersion containing a conductive material (PEDOT / AQS) was used instead of the treatment solution containing a conductive material (PEDOT / PSS) and an additive (AQS).

[0139] Comparative Example 3

[0140] 3,4-ethylenedioxythiophene and AQS as a low molecular weight dopant are dissolved in ion exchange water (liquid component) to prepare a mixed solution. While stirring the mixed solution, iron (III) sulfate (oxidant) dissolved in ion exchange water is added to perform a polymerization reaction. After the reaction, the obtained reaction solution is dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a polymer dispersion containing poly (3,4-ethylenedioxythiophene) doped with AQS (PEDOT / AQS) as the second conductive material.

[0141] In the polymer dispersion containing the first conductive material (PEDOT / PSS), the second conductive material (PEDOT / AQS) was added instead of the additive (AQS). The mixing ratio of the first conductive material and the second conductive material was adjusted so that the amount of AQS contained in the second conductive material was 20 parts by mass per 100 parts by mass of the first conductive material. Except for the above, the electrolytic capacitor B3 was prepared and evaluated in the same manner as in Example 1.

[0142] Table 1 shows the evaluation results of each electrolytic capacitor.

[0143] [Table 1]

[0144]

[0145] For electrolytic capacitor A1, the initial ESR value (X0) after reflow treatment is small, and the ESR value (X1) after high temperature load test is also small, and the increase of ΔESR is suppressed. For electrolytic capacitor A1 in which the solid electrolyte layer contains AQS, since the dedoping of PSS from PEDOT is suppressed, the degradation of the solid electrolyte layer is suppressed, and the increase of ESR is suppressed.

[0146] In the electrolytic capacitor B1 in which the solid electrolyte layer does not contain AQS, dedoping of PSS from PEDOT causes degradation of the solid electrolyte layer, so X0 and ΔESR increase.

[0147] Since the electrolytic capacitor B2 uses PEDOT / AQS as a conductive material, the conductivity of the solid electrolyte layer is low, and X0 and ΔESR are increased compared to the electrolytic capacitors A1, B1, and B3.

[0148] In the electrolytic capacitor B3, since AQS is contained in the solid electrolyte layer in a state of being doped in PEDOT, AQS cannot suppress dedoping of PSS from PEDOT, and X0 and ΔESR increase.

[0149] 《Examples 2 to 8》

[0150] Electrolytic capacitors A2 to A8 were prepared and evaluated in the same manner as in Example 1 except that the amount of additive (AQS) added to the polymer dispersion containing the conductive material (PEDOT / PSS) was set to the value shown in Table 2. The evaluation results are shown in Table 2. It should be noted that the amount of AQS added in Table 2 represents the amount (mass parts) per 100 parts by mass of the conductive material. In addition, the evaluation results of electrolytic capacitors A1 and B1 are also shown in Table 2.

[0151] [Table 2]

[0152]

[0153] Compared with electrolytic capacitor B1, any of electrolytic capacitors A1 to A8 has smaller X0 after reflow treatment and smaller X1 after high temperature load test, and the increase of ΔESR is suppressed. For electrolytic capacitors A3 to A7 in which the amount of AQS added is 1 to 30 parts by mass per 100 parts by mass of conductive material, X0 is smaller and the increase of ΔESR is also suppressed.

[0154] 《Examples 9 to 15》

[0155] Electrolytic capacitors A9 to A15 were prepared and evaluated in the same manner as in Example 1 except that the compounds shown in Table 3 were used instead of anthraquinone-2-sulfonic acid as additives. The evaluation results are shown in Table 3. Table 3 also shows the evaluation results of the electrolytic capacitor A1.

[0156] [Table 3]

[0157]

[0158] Electrolytic capacitors A9 to A15 have small X0 after reflow treatment and small X1 after high temperature load test like electrolytic capacitor A1, and the increase of ΔESR is suppressed. In particular, electrolytic capacitors A1, A9, A10, and A13 have smaller X0 and the increase of ΔESR is suppressed.

[0159] Industrial Applicability

[0160] The present invention can be used for an electrolytic capacitor including a solid electrolyte layer covering at least a portion of a dielectric layer.

Claims

1. An electrolytic capacitor comprising an anode body having a dielectric layer on its surface, and a solid electrolyte layer, The solid electrolyte layer comprises a conductive material and an additive, The conductive material comprises a π-conjugated polymer and a polymer dopant having a first anionic group doped in the π-conjugated polymer. The additive comprises a quinone compound having a second anionic group, The solid electrolyte layer includes the quinone compound which is not doped in a π-conjugated polymer.

2. The electrolytic capacitor according to claim 1, wherein: The solid electrolyte layer includes 1 part by mass or more and 30 parts by mass or less of the quinone compound per 100 parts by mass of the conductive material.

3. The electrolytic capacitor according to claim 1 or 2, wherein: The quinone compound includes at least one compound selected from the group consisting of anthraquinone compounds, naphthoquinone compounds, and benzoquinone compounds.

4. The electrolytic capacitor according to claim 1 or 2, wherein: The quinone compound includes at least one selected from anthraquinone-1-sulfonic acid, anthraquinone-2-sulfonic acid, anthraquinone-2,6-disulfonic acid, anthraquinone-2,7-disulfonic acid, anthraquinone-1,5-disulfonic acid, 1,2-naphthoquinone-4-sulfonic acid, 1,4-benzoquinone-2-sulfonic acid and 1,2-benzoquinone-4-sulfonic acid.

5. The electrolytic capacitor according to claim 1 or 2, further comprising a liquid component, The liquid component contains at least one compound selected from the group consisting of a diol compound and a glycerol compound.

6. The electrolytic capacitor according to claim 1 or 2, wherein: The solid electrolyte layer is formed by impregnating at least a portion of the dielectric layer with a treatment solution containing the conductive material and the additive.

7. A method for manufacturing an electrolytic capacitor according to claim 1, comprising the following steps: In the first step, a conductive material is prepared, which includes a π-conjugated polymer and a polymer dopant having a first anionic group doped in the π-conjugated polymer. In a second step, a treatment solution is obtained which includes the conductive material and a quinone compound having a second anionic group as an additive; and In the third step, the treatment solution is impregnated into at least a portion of the dielectric layer of an anode body having a dielectric layer on a surface, thereby forming a solid electrolyte layer.

Citation Information

Patent Citations

  • Conductive polymer composition, and production method thereof

    JP2015017230A

  • Solid electrolytic capacitor and method for producing the same

    US6351370B1